A Visible‐Light‐Mediated Radical Smiles Rearrangement and its Application to the Synthesis of a Difluoro‐Substituted Spirocyclic ORL‐1 Antagonist. (16th October 2015) - Douglas, James J.; Albright, Haley; Sevrin, Martin J.; Cole, Kevin P.; Stephenson, Corey R. J.
Abstract: A visible‐light‐mediated radical Smiles rearrangement has been developed to address the challenging synthesis of the gem ‐difluoro group present in an opioid receptor‐like 1 (ORL‐1) antagonist that is currently in development for the treatment of depression and/or obesity. This method enables the direct and efficient introduction of the difluoroethanol motif into a range of aryl and heteroaryl systems, representing a new disconnection for the synthesis of this versatile moiety. When applied to the target compound, the photochemical step could be conducted on 15 g scale using industrially relevant [Ru(bpy)3 Cl2 ] catalyst loadings of 0.01 mol %. This transformation is part of an overall five‐step route to the antagonist that compares favorably to the current synthetic sequence and demonstrates, in this specific case, a clear strategic benefit of photocatalysis. Abstract : Eine lichtvermittelte radikalische Smiles‐Umlagerung ermöglicht die Synthese der gem ‐Difluorgruppe eines ORL‐1‐Antagonisten und die Einführung der Difluorethanol‐Einheit in verschiedene (hetero)aromatische Verbindungen. Zur Herstellung des Antagonisten konnte die photochemische Reaktion im 15‐g‐Maßstab mit einer [Ru(bpy)3 ]Cl2 ‐Beladung von 0.01 Mol‐% durchgeführt werden.